The paradox of progress: Technological advancements in banking and the dual impact on SME bank borrowing - Aneta Hryckiewicz; Julia Korosteleva; Łukasz Kozłowski; Malwina Rzepka; Ruomeng Wang (Asian Development Bank Institute (ADBI), 2024)
This study delves into the impact of technological bank innovations on small and medium-sized enterprise (SME) borrowing across the European Union. By analyzing a comprehensive dataset of 179,921 SME-bank lending relationships from 2009 to 2019, we explore the mechanisms through which technological advancements in banking reshape traditional lending practices. Our empirical analysis documents that banks' technological innovations have a more substantial impact on SMEs' long-term credit growth than on their short-term growth, indicating the usefulness of these technologies in providing data that not only reduce information asymmetry but also enhance long-term decision channels. Specifically, blockchain and automation play a crucial role in expanding bank credit to SMEs. However, we also identify a paradoxical dual effect: while technological advancements facilitate credit access, they simultaneously increase the cost of borrowing for SMEs. This finding highlights a complex interplay where technological progress in banking presents both opportunities and challenges, especially for more opaque firms seeking financing. Our study contributes to the understanding of the nuanced role of innovation in banking, offering insights into the dualistic nature of the impact of technology on SME financing.
Keywords: G21; O16; O33; G23; G32; 330; SME financing; bank technology; innovation; collateral; cost of intermediation